Insulin‐like growth factor‐1 promotes osteogenic differentiation and collagen I alpha 2 synthesis via induction of mRNA‐binding protein LARP6 expression. (17th February 2017) - Guo, Yue; Tang, Chen‐Yi; Man, Xiao‐Fei; Tang, Hao‐Neng; Tang, Jun; Zhou, Ci‐La; Tan, Shu‐Wen; Wang, Min; Feng, Yun‐Zhi; Zhou, Hou‐De
Abstract : This study explored the mechanism underlying the stimulation of collagen synthesis and osteoblastic differentiation by insulin‐like growth factor 1 (IGF1) in primary mouse osteoblasts. Primary mouse calvarial osteoblasts were cultured and treated with various doses of IGF1 before transfection with siRNA targeting the collagen type I alpha 2 ( Col1a2 ) or La ribonucleoprotein domain family member 6 ( Larp6 ) genes. Alkaline phosphatase (ALP) activity, osteocalcin staining, alizarin red quantification and the expression level of runt‐related transcription factor 2 (RUNX2) were performed to assess the differentiation of pre‐osteoblasts. Based on Western blot analysis, IGF1 up‐regulated COL1A2 protein expression in the primary osteoblasts in a dose‐ and time‐dependent manner. In addition, Col1a2 interference inhibited the differentiation and mineralization of osteoblasts. IGF1 also stimulated the differentiation of mouse primary osteoblasts and increased LARP6 expression during osteogenic differentiation. RNA‐Immunoprecipitation (IP) indicated that LARP6 could bind to Col1a2 mRNA after IGF1 stimulation. However, transfection of Larp6 ‐specific siRNA significantly reduced collagen and ALP secretion, mineralization and inhibited the expression of osteocalcin and RUNX2, indicating that Larp6 interference inhibited the differentiation ability of primary mouse calvarial osteoblasts, and these effects could not be reversed by IGF1. Thus, IGF1 could promote COL1A2 expression and osteoblast differentiation in primary mouse calvarial pre‐osteoblasts by increasing LARP6 expression via a posttranscriptional mechanism. Abstract : IGF1 promotes primary osteoblast differentiation and Col1a2 expression. IGF1 induces LARP6 expression. LARP6 regulates Col1a2 expression and primary osteoblast differentiation.